From admission to empowerment: A proposed framework for enhancing the enrollment requirements of deaf and hard-of-hearing students in higher education - Albash, Nourah Ibrahim Abdullah (International Journal of Innovative Research and Scientific Studies, 2025)
In light of global efforts toward achieving inclusive and equitable education for all, there is an increasing need to shed light on the current state of higher education for deaf and hard-of-hearing (DHH) students and to analyze the challenges they face in order to contribute to the development of more inclusive educational environments. The present study aimed to identify the essential requirements for enrolling deaf and hard-of-hearin (DHH) students in higher-education institutions, and examine potential differences from the perspective of teachers according to their educational qualifications and years of experience. The study employed a descriptive survey research design using a researcher-developed questionnaire administered to 61 female teachers of DHH students in Saudi Arabia (Al-Ahsa Governorate). Data were analyzed using descriptive and inferential statistics to determine teachers’ perceptions. The findings revealed a high level of agreement among teachers’ participants regarding the importance of all identified domains. The most critical requirements for enrolling DHH students in higher education were ranked, in descending order, as follows: requirements related to the educational process, the educational environment, faculty members, sign-language interpreters and administrative aspects, and financial requirements. No statistically significant differences were observed in teachers’ views based on their educational qualifications and years of experience. The study concludes that achieving effective inclusion of DHH students in higher education requires comprehensive and coordinated efforts across multiple educational, institutional, and societal dimensions. Practically, the study proposes a framework to enhance institutional readiness by improving instructional strategies, ensuring accessible learning environments, providing qualified interpreters, Expanding Education and Training Opportunities, Effective Leadership, Infrastructure Developmen, Improving Attitudes, and allocating adequate financial resources, along with institutional and policy-level commitment, thereby supporting inclusive education in alignment with national and global goals.